Optimal cytoreduction for advanced epithelial ovarian cancer - N. G. Kormosh; K. P. Laktionov; N. S. Kerzhkovskaya (Опухоли женской репродуктивной системы, 2014)
This article is review of literature on role of surgery in the initial management of advanced stage ovarian cancer, focusing on the definition of optimum surgical cytoreduction, assessment of resectability, estimation of the risk of postoperative complications. Analyze of published scien- tific data suggest that removal of all evidence of macroscopic disease should be the goal of primary or interval cytoreductive surgery.